2017
DOI: 10.1103/physrevb.95.035305
|View full text |Cite
|
Sign up to set email alerts
|

Light-hole exciton in a nanowire quantum dot

Abstract: Quantum dots inserted inside semiconductor nanowires are extremely promising candidates as building blocks for solid-state based quantum computation and communication. They provide very high crystalline and optical properties and offer a convenient geometry for electrical contacting. Having a complete determination and full control of their emission properties is one of the key goals of nanoscience researchers. Here we use strain as a tool to create in a single magnetic nanowire quantum dot a light-hole excito… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 42 publications
4
34
0
Order By: Relevance
“…On the other hand, the ordering of the VB states may be significantly altered and even reversed when the QDs are embedded in the core/shell NW, where the strain that is created due to the lattice mismatch between the core and shell materials is uniaxial along the NW axis [19].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the ordering of the VB states may be significantly altered and even reversed when the QDs are embedded in the core/shell NW, where the strain that is created due to the lattice mismatch between the core and shell materials is uniaxial along the NW axis [19].…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, the LH ground state was obtained in a GaAs QD with a tensile stress applied in-plane by a piezoelectric device [21,22]. The ground state is also a light-hole in an elongated QD with a compressive mismatch, as shown theoretically [23][24][25] and demonstrated experimentally in QDs embedded in a * joel.cibert@neel.cnrs.fr nanowire [16]. In the first case, the applied strain must overcompensate the built-in strain and the confinement; in the second case, they all play into the same direction.…”
Section: Introductionmentioning
confidence: 97%
“…Recent studies have demonstrated the interest of a more accurate positioning in a waveguiding nanowire [7,8] and even the possibility to insert the structure into a complete optical circuit [9][10][11]. Such nanowires containing a QD have been grown mostly from InP [7,8,12,13], but nanowire-QDs have been also demonstrated with other materials such as CdSe [14], or CdTe [15,16]. Particularly sharp lines are obtained in the case of III-Vs.…”
Section: Introductionmentioning
confidence: 99%
“…The strong electronhole interaction gives rise to a large excitonbiexciton splitting, so that single photon emission was demonstrated up to room temperature in CdSe quantum dots embedded in a ZnSe nanowire. 40 This dot-nanowire configuration in CdTe-ZnTe allows one to adjust the built-in strain in order to manipulate the magnetic properties introduced through Mn impurities 41,42 or to control the light-hole heavy-hole character of the ground state 43 for an increased flexibility of the optical and spin properties. ZnTe nanowires can be grown by MBE using a gold seed, on GaAs or Si substrates, [44][45][46] where the growth mode is assumed to be VLS due to the formation of a eutectic of gold with gallium or silicon, or on ZnTe buffer layer, 47 where the growth mode is assumed to be VSS.…”
mentioning
confidence: 99%